Enlightened virginity in eighteenth-century literature - Harol, Corrinne (Palgrave Macmillan, 2006)
"Enlightened Virginity in Eighteenth-Century Literature" analyzes the history of the English virgin at the height of her celebrity. In so doing, it presents new arguments about the early English novel and its relationship to science, religion, and feminist theory.